Performance of coconut hybrids and varieties in the East coast of Andhra Pradesh - Kireeti, A.; Ramanandam, G.; Bhagavan, B.V.K.; Rao, N.B.V. Chalapathi; Neeraja, B.; Rao, V. Govardhan; Srinivasulu, B.; Jerard, B Augustine (Journal of Plantation Crops, 2023)
Coconut (Cocos nucifera L.) is one of the plantation crops with more life span, so suitability of a variety or hybrid for particular region may improve the productivity of the coconut. An experiment was carried out with seven hybrids and two varieties viz. Chandra Sankara (COD × WCT), Chandra Laksha (LCT x COD), VHC1 (ECT × MGD), VHC-2 (ECT × MYD), Kera Ganga (WCT × GBGD), Laksha Ganga (LCT × GBGD), Godavari Ganga (ECT x GBGD), Kera Chandra (Double Century) and Chandra Kalpa at Dr.YSRHUHorticultural Research Station, Ambajipeta, Dr. B. R. Ambedkar Konaseema Dist., Andhra Pradesh. The experiment was initiated in 2002, in Randomized Block Design in three replicated blocks. The compiled data for six years (2015- 2021) revealed that, Godavari Ganga recorded significantly highest nut yield /palm/year (144.40 nuts) followed by VHC-2 (134.93 nuts) and Kera Ganga (133.33 nuts). Godavari Ganga recorded maximum copra yield of 3.20 t/ha and oil yield of 2.20 t/ha. Tender nut water quantity was recorded more (322.5 mL) in VHC-2 and Godavari Ganga. Due to its superior nut, copra and oil yield, Godavari Ganga and VHC-2 can be recommended for cultivation Andhra Pradesh.